Effect of MgO/ZnO ratio on the formation process of MgxZn1-xO ceramics - N. Korsunska; Yu. Polishchuk; S. Ponomaryov; K. Kozoriz; S. Chusnutdinow; O. Melnichuk; L. Melnichuk; L. Khomenkova (Heliyon, 2024)
The structural characteristics, chemical composition, and element spatial distribution in MgxZn1-xO ceramics were investigated using X-ray diffraction, scanning electron microscopy, Auger electron spectroscopy, energy-dispersive X-ray spectroscopy, and cathodoluminescence techniques. The study revealed that the morphology of the ceramic samples, as well as the mechanism of solid solution formation, depend on the relative contribution of both oxides in the charge. It was discovered that hexagonal and cubic phases of the solid solution were found to form simultaneously. An increase in the MgO content in the charge results in the magnesium content rise in the hexagonal grains continuously, reaching approximately 13 at.%. It was discovered an enrichment of grain boundaries with zinc and magnesium playing a significant role in doping ZnO and MgO grains. Obtained results allowed to propose two mechanisms involved in the formation of solid solution ceramics: i) diffusion of Mg and Zn along grain boundaries, followed by their incorporation into ZnO or MgO grains, respectively, and ii) interdiffusion of Mg into ZnO and Zn into MgO due to direct contact of ZnO and MgO grains. The second mechanism appears to dominate when both ZnO and MgO contribute comparably, increasing the probability of their direct contact. This study significantly advances the understanding of the process of the formation of MgxZn1-xO ceramics under thermodynamic conditions. These insights are crucial for optimizing the doping process and improving the material properties, thereby promoting innovations in the ceramics industry.